Group a Rotaviruses in Children with Gastroenteritis in a Canadian Pediatric Hospital: The Prevaccine Era - Estelle Chetrit; Yvan L’Homme; Jagdip Singh Sohal; Caroline Quach (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: A publicly funded, group A rotavirus (RVA) vaccination program was implemented in Quebec in November 2011.